2021
DOI: 10.1088/1757-899x/1200/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Talent as a Spearhead of Construction 4.0 Transformation: Analysis of Their Challenges

Abstract: Global industries are investing in technology to accelerate digital transformation. Construction is also most likely to be digitalised based on current technology trends. However, technology adoption is not the only ingredient to successfully transform the construction industry towards the fourth industrial revolution (4IR). This transformation requires additional changes for the employees. It is expected to significantly impact the talent landscape, ranging from job categories to skill sets. While this transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Apart from this, the authors recommend technological training programs to increase awareness of the Construction 4.0 revolution and highly recommend that associations and organizations take proactive steps to attract highly skilled personnel, promote efficiency, and facilitate the intergenerational exchange of knowledge. The notion that upskilling and reskilling training sessions enhance the performance of an organization's workforce is reinforced in [12]. These sessions provide a foundation for continuous learning, background knowledge on Industry 4.0-related skills, and a future-ready workforce.…”
Section: Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, the authors recommend technological training programs to increase awareness of the Construction 4.0 revolution and highly recommend that associations and organizations take proactive steps to attract highly skilled personnel, promote efficiency, and facilitate the intergenerational exchange of knowledge. The notion that upskilling and reskilling training sessions enhance the performance of an organization's workforce is reinforced in [12]. These sessions provide a foundation for continuous learning, background knowledge on Industry 4.0-related skills, and a future-ready workforce.…”
Section: Policymentioning
confidence: 99%
“…[49] recognizes reskilling and upskilling as essential components of digitalization in the construction industry, while Ref. [12] proposes a holistic shift in education, skills development, awareness, and competencies. Government intervention is needed to define the necessary skills and ensure strategic alignment between digital transformation and the workforce.…”
Section: Policymentioning
confidence: 99%
“…According to [127], there is a skill gap in the industry relating to Construction 4.0 technologies. The study identified nine factors that impact the adoption of these technologies, including a lack of awareness or clarity concerning Industry 4.0, low job security for skilled workers, and dependence on outside talent.…”
Section: ) Training Sessionsmentioning
confidence: 99%